Potential biomarker in serum for predicting susceptibility to type 2 diabetes mellitus: Free fatty acid 22:6. Issue 6 (4th December 2020) - Ma, Yinghua; Xiong, Jianyu; Zhang, Xueting; Qiu, Tongtong; Pang, Huai; Li, Xue; Zhu, Jiaojiao; Wang, Jingzhou; Pan, Chongge; Yang, Xin; Chu, Xiaolong; Yang, Bingqi; et al.
Abstract: Aims/Introduction: Type 2 diabetes mellitus is closely linked to increased levels of free fatty acids (FFAs) in obese individuals, although which FFA is most associated with type 2 diabetes mellitus is unclear. This study aimed to identify the specific FFAs that best predict the occurrence of type 2 diabetes mellitus in obese individuals, and assess their potential application value. Materials and Methods: Participants were divided into three groups: a normal weight group ( n  = 20), an obese group ( n  = 10) and a type 2 diabetes mellitus group ( n  = 10). FFAs in serum samples were determined by ultra‐high‐pressure liquid chromatography–mass spectrometry, and orthogonal partial least squares discriminant analysis models were used to study the FFA profile among the three groups. Results: Compared with the normal weight group, 14 FFAs (C8:0/10:0/14:0/16:1/18:1/20:2/ 20:3 /20:4/ 20:5/ 22:6/7:0/9:0/11:0 and C13:0) were significantly increased in the obese group, and nine FFAs (C14:0, C18:1, C20:1, C 18:2, C20:2, C20:3, C18:3, C20:5 and C22:6) were significantly increased in the type 2 diabetes mellitus group. Subsequently, the Venn diagram results showed that six FFAs (C14:0, C18:1, C20:2, C20:3, C20:5 and C22:6) were significantly increased in both the obese and type 2 diabetes mellitus groups. Among these six, C22:6 was finally identified as an independent risk factor for type 2 diabetes mellitus, and had a great potential to predict the susceptibility to type 2 diabetes mellitus (area under the curve 0.803). Conclusions: C22:6 can be an independent risk factor for type 2 diabetes mellitus, and it has a great potential to predict the susceptibility to type 2 diabetes mellitus. Abstract : Our aim was to identify the different free fatty acids among the normal weight group, obese group and type 2 diabetes mellitus group. We finally found that C22:6 has a better ability to predict the susceptibility to type 2 diabetes mellitus, which is the key risk factor for type 2 diabetes mellitus caused by obesity.